2012
DOI: 10.1007/s10936-012-9231-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Narrative Discourse Structure as an Ecologically Relevant Measure of Executive Function in Adults

Abstract: This study examined the narrative discourse production and executive function (EF) abilities of 46 neuro-typical adults (18-98 years old). Two questions were addressed: Is the analysis of narrative structure sensitive to changes associated with aging? & What is the relationship between measures of narrative structure and EF? Narratives were elicited under two conditions and narrative structure was analyzed for the presence of organizing story grammar elements. Narrative structure was significantly correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 67 publications
3
40
0
6
Order By: Relevance
“…Aging presumably affects word retrieval not only in isolation but also in context (e.g., Mortensen, Meyer, & Humphreys, 2006). However, most research on connected speech production in healthy aging has addressed aspects of communication such as discourse structure (e.g., Cannizzaro & Coelho, 2013), off-topic speech (e.g., Arbuckle & Gold, 1993; Arbuckle, Nohara-LeClaire, & Pushkar, 2000; Pushkar, Basevitz, Arbuckle, Nohara-LeClaire, Lapidus, & Peled, 2000; Pushkar-Gold & Arbuckle, 1995), or information content (e.g., Wright, Capilouto, Srinivasan, & Fergadiotis, 2011), and did not focus specifically on word retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Aging presumably affects word retrieval not only in isolation but also in context (e.g., Mortensen, Meyer, & Humphreys, 2006). However, most research on connected speech production in healthy aging has addressed aspects of communication such as discourse structure (e.g., Cannizzaro & Coelho, 2013), off-topic speech (e.g., Arbuckle & Gold, 1993; Arbuckle, Nohara-LeClaire, & Pushkar, 2000; Pushkar, Basevitz, Arbuckle, Nohara-LeClaire, Lapidus, & Peled, 2000; Pushkar-Gold & Arbuckle, 1995), or information content (e.g., Wright, Capilouto, Srinivasan, & Fergadiotis, 2011), and did not focus specifically on word retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of narrative discourse ability in healthy aging populations have found that performance on global (i.e., macro-level) measures is correlated with age and performance on a number of cognitive tasks. Cannizzaro and Coelho (2012) found that the proportion of T-units in episode structure, a measure of narrative organization (i.e., story grammar) that has demonstrated sensitivity to TBI (Coelho, 2002;, decreased with age and was associated with both linguistic and nonlinguistic measures of EF, such as verbal fluency and design fluency. In Wright and colleagues' study (2011), younger and older adults did not differ in the proportion of story propositions produced.…”
mentioning
confidence: 99%
“…Cognitive processes and domains, such as working memory (WM), declarative memory, executive functions (EF), and general intelligence have been shown to correlate with or predict narrative ability at multiple levels of analysis (e.g., Cannizzaro & Coelho, 2012;Chapman et al, 2006;Coelho et al, 2013;Kurczek & Duff, 2011;Wright, Capilouto, Srinivasan, & Fergadiotis, 2011). Studies of narrative discourse ability in healthy aging populations have found that performance on global (i.e., macro-level) measures is correlated with age and performance on a number of cognitive tasks.…”
mentioning
confidence: 99%
“…Uma grande variedade de discursos e medidas tem sido pesquisada, interesse esse influenciado pelo reconhecimento de que o discurso é uma forma natural de comunicação e pode fornecer informações importantes sobre a integração de habilidades linguístico-cognitivas, como nomeação, e também sobre habilidades de seleção, organização e planejamento (Andreetta et al, 2012;Wills et al, 2012;Cannizzaro, Coelho, 2013).…”
Section: Importância Do Estudo Do Discursounclassified
“…A utilização de figuras para eliciar o discurso tem sido considerada uma maneira eficiente de se obter amostras de discurso padronizadas entre diversos indivíduos (Giles et al, 1996;March et al, 2006;Cannizzaro, Coelho, 2013). O uso de figuras é uma ferramenta bastante válida para eliciar amostras de fala encadeada, que se aproximam da conversação natural (Duong et al, 2003).…”
Section: Discurso Narrativounclassified